E-Invoicing in Tax Accounting: A Bibliometric Analysis of Research Trends (2005–2026) - Loso Judijanto; Anton Susilo (Westscience Press, 2026)
This study aims to examine the development and intellectual structure of research on e-invoicing in tax accounting through a bibliometric analysis covering the period 2005–2026. Data were collected from the Scopus database using relevant keywords related to electronic invoicing and digital taxation. The dataset was analyzed using VOSviewer to map publication trends, keyword co-occurrence, thematic evolution, and research clusters. The results indicate that e-invoicing has emerged as a central theme closely linked to taxation, digital transformation, and compliance systems, particularly in the context of value-added tax (VAT). The findings also reveal a clear evolution of research focus, from early discussions on transactional and operational aspects toward more recent emphasis on digital reporting requirements, regulatory frameworks, and platform-based taxation. Density analysis shows that while core themes such as taxation and digitalization are well-established, emerging areas including decision-making, sector-specific applications, and advanced technologies remain underexplored. This study contributes to the literature by providing a comprehensive mapping of the field and identifying future research opportunities, particularly in integrating interdisciplinary perspectives and emerging digital technologies to enhance tax system effectiveness.